Hubungan Kecanduan Media Sosial terhadap Kejadian Cyberbullying pada Remaja di Kota Semarang - Salwa Aiza Zahra; Betie Febriana; Wahyu Endang (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2026)
Excessive use of social media among adolescents may lead to addiction, which increases the risk of aggressive online behavior such as cyberbullying. This study aims to anlyze the relationship between social media addiction and the incidence of cyberbullying among adolescents in Semarang City. A quantitative method with a cross-sectiona. design was employed, involving 320 high school students from four public schools in semarang. Date were collected using the Social Media Addiction Scale–Student Form (SMAS–SF) and the Cyber Victimization Scale (CVS). Data were analyzed using the Spearman Rank correlation test. The results revealed a significant relationship between social media addiction and cyberbullying (r = 0,368; p = 0,000). This finding indicates that higher levels of social media addiction are associated with greater involvement in cyberbullying, both as perpetrators and victims. In comclusion, social media addiction contributes to the rise of cyberbullying behavior among adolescents. It is recommended that adolescents improve self-control and digital literacy, while parents and educational institutions enhance supervision and education on responsible sociam media use.